Pengaruh Ukuran Perusahaan, Volume Perdagangan Saham, Volatilitas Return Saham, dan Dividend Yield terhadap Bid-Ask Spread - Pebra Perdana Rio; Fitria Husnatarina; Rini Oktavia (Jurnal Pasar Modal dan Bisnis, 2020)
Bid-Ask Spread actually measures asymmetric information or asymmetric information between brokers and investors. The size of the Bid-Ask Spread shows how much asymmetric information among market participants. To reduce the level of asymmetric information, market participants try to get certain signals that can be used as information to reduce uncertainties. This study aims to analyze the effect of Company Size, Stock Trading Volume, Stock Return Volatility and Dividend Yield on Bid-Ask Spread partially on manufacturing companies listed on the Indonesia Stock Exchange for the period 2014-2018. Data is taken from the Indonesia Stock Exchange website. The population in this study is manufacturing companies listed on the Indonesia Stock Exchange until the period 2018. The sample in this study amounted to 30 companies for 5 years. Samples were obtained by purposive sampling method. The analytical method in this research is descriptive statistical analysis, multiple linear regression analysis, classic assumption test and hypothesis testing using IBM SPSS 24 software. Based on the test results show that partially company size and stock trading volume have a negative and significant effect on bid-ask spread, while stock return volatility has a positive and significant effect on the bid-ask spread, but the dividend yield does not affect the bid-ask spread.